Occupational Risk of Knee Osteoarthritis Among Pedicab Operators: A Cross-Sectional Study in Indonesia - Harahap, Rudiansyah; Setiawan, Muhammad Riza; Fatharani, Lukman Faishal; Putri, Hayyin Assofa Amina (Pusat Pengembangan Teknologi Informasi dan Jurnal Universitas Muhammadiyah Palu, 2025)
Introduction: Osteoarthritis is a joint disease with multifactorial causes, particularly among pedicab operators. Movements such as pushing, pedaling, and lifting often cause damage to cartilage, ligaments, and synovial tissues. This study evaluates the risk of knee OA (Osteoarthritis) from the perspective of pedicab operators, a profession whose health is often neglected, by assessing work duration, length of work, footwear usage, and work posture. Methods: This cross-sectional study was carried out on 50 pedicab operators based on inclusion and exclusion criteria. The demographic questionnaire used to assess work duration, length of work, footwear usage, and type of road. The posture was evaluated using the REBA Worksheet by measuring the angles of the neck, legs, body, wrists, upper arms, and lower arms. The risk of developing knee osteoarthritis was assessed using KOOS questionnaire. The data obtained was analyzed using SPSS version 26 and Graphpad. Results: 48.3% are aged 45–50 years, with 69% having a work posture with a moderate risk level. 51.7% of pedicab operators were at risk for Knee OA. Data analysis found that there was a relationship between work posture (p = 0.01) and length of work (0.000) with the risk of OA, and there is a significant difference between OA scores for those wearing sandals compared to shoes. Conclusion: The pedicab drivres have a risk of developing knee osteoarthritis through their length of work, footwear and work posture. This study stands out due to its biomechanical assessment, providing a detailed analysis of the factors contributing to the risk. The practical implications of this research underscore the importance of incorporating these findings into occupational health policies to enhance the well-being of pedicab operators and mitigate the risk of work-related musculoskeletal disorders. Furthermore, the study contributes to the broader discourse on occupational health, highlighting the need for targeted interventions and policy changes to protect workers in physically demanding jobs.